Vertical targeting of the PI3K/AKT pathway at multiple points is synergistic and effective for non-Hodgkin lymphoma - Kupcova, Kristyna; Senavova, Jana; Jura, Filip; Herman, Vaclav; Rajmonova, Anezka; Pacheco-Blanco, Mariana; Chrbolkova, Tereza; Hamova, Iva; Davis, R Eric; Havranek, Ondrej (Experimental hematology & oncology, 2024)
The phosphatidylinositol 3‐kinase/protein kinase B (PI3K/AKT) signaling pathway is critically active in many cell types, both normal and neoplastic. Many small-molecule inhibitors targeting different levels of the PI3K/AKT pathway have been developed for cancer therapy, but their efficacy is reduced by compensatory pathway re-activation mechanisms, and their tolerability by toxic side effects. We studied this problem using cell lines representing diffuse large B-cell lymphoma (SUDHL-4 and OCI-Ly7), a genetically-encoded live-cell reporter of AKT activity, and 3 small-molecule inhibitors targeting different levels of the pathway: idelalisib (PI3Kδ), GSK2334470 (PDPK1), and ipatasertib (AKT). Half-maximal (IC50) concentrations of these inhibitors for AKT activity inhibition at 1 h, when used individually, were much lower than their IC50 values for reduction of viable cell number after 4 days. Time-course studies explained this discrepancy: AKT activity in the continuous presence of the inhibitors returned to normal after 24 h, and was supranormal after inhibitor removal. Combining all 3 inhibitors produced sustained inhibition of AKT activity, was broadly synergistic at reducing viable cell number, enabled substantially lower doses of each inhibitor to be used, and was enhanced further by the mTOR inhibitor rapamycin. Moreover, combined PDPK1 and AKT inhibition showed synergy with multiple different PI3K inhibitors. In a syngeneic mouse cell line model of lymphoma (A20), the triple combination showed antitumor activity and no evidence of toxicity. Our findings provide proof of concept suggesting further study of the safety and efficacy of low-dose multilevel PI3K/AKT pathway inhibition, for lymphoma and perhaps other cancers.